54.2: A Novel Flat‐Type Transparent Liquid Crystal Display. Issue 1 (June 2015) - Kuo, Chia‐Wei; Liao, Yi‐Yang; Tseng, Bo‐Shiang; Lin, Ching‐Huan; Lai, Yi‐Hsiang; Chuang, Chin‐Tang; Yeh, Cheng‐Nan; Sugiura, Norio
Abstract : In this paper, a novel transparent light guide has been developed. Concave microstructures with partially random distribution were designed to reflect incident light and prevent moiré issue. Furthermore, a 12.1‐inch RGBW LCD was combined with the transparent light guide to demonstrate the transparent tablet scenario.